2022
DOI: 10.3390/ijms23094562
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between β-Catenin and CCL2 Drives Migration of Monocytes towards Glioblastoma Cells

Abstract: Isocitrate dehydrogenase (IDH)-wildtype glioblastoma (GBM) is a fast growing and highly heterogeneous tumor, often characterized by the presence of glioblastoma stem cells (GSCs). The plasticity of GSCs results in therapy resistance and impairs anti-tumor immune response by influencing immune cells in the tumor microenvironment (TME). Previously, β-catenin was associated with stemness in GBM as well as with immune escape mechanisms. Here, we investigated the effect of β-catenin on attracting monocytes towards … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 87 publications
0
7
0
Order By: Relevance
“…The role of MCP-1 in GAMs has been verified by various in vivo and in vitro studies, where the MCP-1 expression level is highly correlated with the grade of glioma ( 66 ). A recent study indicated that the cooperation between β- Catenin and MCP-1 may be responsible for the rapid and highly heterogeneous growth of Isocitrate dehydrogenase wildtype GBM ( 72 ). M-CSF is another important chemokine, which not only promotes the mobility of GAMs but also mediates the M2 polarization of GAMs ( 73 ).…”
Section: Interaction Between Gams and Gbm Cellsmentioning
confidence: 99%
“…The role of MCP-1 in GAMs has been verified by various in vivo and in vitro studies, where the MCP-1 expression level is highly correlated with the grade of glioma ( 66 ). A recent study indicated that the cooperation between β- Catenin and MCP-1 may be responsible for the rapid and highly heterogeneous growth of Isocitrate dehydrogenase wildtype GBM ( 72 ). M-CSF is another important chemokine, which not only promotes the mobility of GAMs but also mediates the M2 polarization of GAMs ( 73 ).…”
Section: Interaction Between Gams and Gbm Cellsmentioning
confidence: 99%
“…CCL2 and its related receptor (CCR2) promote the migration of brain tumors and monocytes across the vascular endothelium (Vakilian et al, 2017;Cho et al, 2019). Besides, Aretz et al (Aretz et al, 2022) demonstrated that the cross-talk between CCL2 and β-catenin could affect the dryness and immune escape mechanism of GBM by regulating the activity of immune cells and glioblastoma stem cells. In animal models, mNOX-E36 blocked angiogenesis and macrophage recruitment, and tumor volume and blood volume were reduced.…”
Section: Figurementioning
confidence: 99%
“…Endogenous cells are potentially powerful tools for delivering therapeutic agents to specific brain targets. Bone marrow-derived circulating monocytes (BMDMs) are the primary source of TAMs in GBMs, with the natural ability to traverse the BBB/BTB and penetrate brain tumor sites, and they mainly target vascular-free, necrotic/hypoxic areas in tumors . RT, as the mainstay for brain tumor management, can promote chemotaxis of monocytes by upregulating monocyte chemokine-1 (MCP-1)/C-C basal chemokine ligand 2 (CCL-2) expression in the tumor region. , Therefore, it can be hypothesized that monocytes can act as carriers to deliver drugs to brain tumors in the presence of chemokines.…”
Section: Introductionmentioning
confidence: 99%